2021
DOI: 10.1111/hel.12843
|View full text |Cite
|
Sign up to set email alerts
|

Dietary multivalent anti‐Helicobacter pylori immunoglobulin Y significantly increase the H. pylori eradication and improve the clinical symptoms in patients

Abstract: Background The oral chicken immunoglobulin Y (IgY) as a novel model of immunotherapy to control Helicobacter pylori (H. pylori, Hp) infection has gained much interest in recent years. However, none of the current IgY therapies showed a total eradication of H. pylori on patients. Methods In this report, the recombinant antigens of H. pylori, including UreB (1710 bp), BabA2 (1269 bp), and FlaA (399 bp), were, respectively, expressed and purified, and then mixed and subjected to immunize laying hens for the prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Effects against H. pylori by specific IgY have also been investigated both in vitro and in vivo. These studies mainly focus on the treatment of H. pylori 15–21 . Comprehensive consideration of the intercepting effect of gastric mucus, the proteolysis by low pH, and pepsin, as well as the normal emptying of the stomach, we believe that it is difficult to have enough active IgY to reach the gastric pit where H. pylori mainly colonized, and the therapeutic efficacy to eradicate H. pylori is constrained 22–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects against H. pylori by specific IgY have also been investigated both in vitro and in vivo. These studies mainly focus on the treatment of H. pylori 15–21 . Comprehensive consideration of the intercepting effect of gastric mucus, the proteolysis by low pH, and pepsin, as well as the normal emptying of the stomach, we believe that it is difficult to have enough active IgY to reach the gastric pit where H. pylori mainly colonized, and the therapeutic efficacy to eradicate H. pylori is constrained 22–26 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies mainly focus on the treatment of H. pylori. [15][16][17][18][19][20][21] Comprehensive consideration of the intercepting effect of gastric mucus, the proteolysis by low pH, and pepsin, as well as the normal emptying of the stomach, we believe that it is difficult to have enough active IgY to reach the gastric pit where H. pylori mainly colonized, and the therapeutic efficacy to eradicate H. pylori is constrained. [22][23][24][25][26] However, IgY has the advantages of cost-effective, convenience, high yield, high binding specificity, and low cross-reactivity.…”
Section: Introductionmentioning
confidence: 99%
“… Attallah et al (2009) found that yolk antibodies (IgY-Hp58) obtained from H. pylori -stimulated immunization effectively inhibited H. pylori infection and alleviated gastritis in BALB/c mice. Another clinical study showed that oral anti-Hp mIgY for 2 weeks reduces urea breath test values and inhibits H. pylori activity ( Guo et al, 2021 ). Currently, Ig Y is used as an oral passive immunotherapy for preventing and controlling gastric and oral infections, with active applications in treating viral diarrhea and other gastrointestinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Aiba et al ( 2019 ) found the combination of anti- Helicobacter pylori (Hp) IgY and Lactobacillus johnsonii No.1088 showed a synergistic effect in anti-Hp activity both in vitro and in vivo. A clinical study was investigated by Guo et al ( 2021 ) on the efficiency of oral multivalent anti-Hp IgY agaist Hp infections. The clinical symptoms in patients were obviously enhanced through a two-week dietary of anti-Hp IgY and Hp eradication reached 30.6%.…”
Section: Introductionmentioning
confidence: 99%